Novel Molecular Determinants of Response or Resistance to Immune Checkpoint Inhibitor Therapies in Melanoma - Zhang, Wenjing; Kong, Yujia; Li, Yuting; Shi, Fuyan; Lyu, Juncheng; Sheng, Chao; Wang, Suzhen; Wang, Qinghua (Frontiers in Immunology, 2022)
Background: Immune checkpoint inhibitor (ICI) therapy dramatically prolongs melanoma survival. Currently, the identified ICI markers are sometimes ineffective. The objective of this study was to identify novel determinants of ICI efficacy. Methods: We comprehensively curated pre-treatment somatic mutational profiles and clinical information from 631 melanoma patients who received blockade therapy of immune checkpoints (i.e., CTLA-4, PD-1/PD-L1, or a combination). Significantly mutated genes (SMGs), mutational signatures, and potential molecular subtypes were determined. Their association with ICI responses was assessed simultaneously. Results: We identified 27 SMGs, including four novel (COL3A1, NRAS, NARS2, and DCC) that associated with ICI efficacy and well-known driver genes. COL3A1 mutations were associated with improved ICI overall survival (HR: 0.64, 95% CI: 0.45-0.91, P = 0.012), whereas immune resistance was observed in patients with NRAS mutations (HR: 1.42, 95% CI: 1.10-1.82, P = 0.006). The presence of the tobacco smoking-related signature was significantly correlated with inferior prognoses (HR: 1.42, 95% CI: 1.11-1.82, P = 0.005). In addition, the signature resembling that of alkylating agents and a newly discovered signature both exhibited extended prognoses (both HR < 1, P < 0.05). Based on the activities of the extracted 6 mutational signatures, we identified one immune subtype that was significantly associated with better ICI outcomes (HR: 0.44, 95% CI: 0.23-0.87, P = 0.017). Conclusion: We uncovered several novel SMGs and re-annotated mutational signatures that are linked to immunotherapy response or resistance. In addition, an immune subtype was found to exhibit favorable prognoses. Further studies are required to validate these findings.